Exxon Valdez Oil Spill: Fate and Effects in Alaskan Waters 1995
DOI: 10.1520/stp19879s
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oil-Affected Habitats by Birds After the Exxon Valdez Oil Spill

Abstract: This study investigated the effects of the Exxon Valdez oil spill on the use of oil-affected habitats by birds during 1989–1991. We measured densities of birds in bays that had been subjected to various levels of oiling from the spill during survey cruises that were conducted throughout the year in Prince William Sound (PWS) and during summer along the Kenai Peninsula. Overall, 23 of 42 (55%) species in PWS and 22 of 34 (65%) species on the Kenai showed no evidence of oiling impacts on their use of habitats. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…Within weeks of the oil spill, concerns were expressed about potential persistent adverse toxic effects on Harlequin Ducks from ingesting oiled prey, especially mussels (Patten et al 2000). Some studies conducted several years after EVOS have reported decreased abundance, attributing it to: 1) reduced overwintering survival of females and/or unsuccessful reproduction caused by EVOS (Esler et al 2002; Patten et al 2000), 2) degraded habitat quality not associated with EVOS (Day et al 1995, 1997; Irons et al 2000; Wiens et al 2004), or 3) exposure to hydrocarbons and, by inference, continuing toxic effects from EVOS, as indicated by elevated cytochrome P4501A [CYP1A] activity (Trust et al 2000; Esler et al 2002; Esler 2008; Esler and Iverson 2010). Based on a weight-of-evidence evaluation from several studies, Wiens et al (2010) concluded no indication of continuing population-level impacts, in terms of either abundance or demographics, on Harlequin Ducks from EVOS.…”
Section: Introductionmentioning
confidence: 99%
“…Within weeks of the oil spill, concerns were expressed about potential persistent adverse toxic effects on Harlequin Ducks from ingesting oiled prey, especially mussels (Patten et al 2000). Some studies conducted several years after EVOS have reported decreased abundance, attributing it to: 1) reduced overwintering survival of females and/or unsuccessful reproduction caused by EVOS (Esler et al 2002; Patten et al 2000), 2) degraded habitat quality not associated with EVOS (Day et al 1995, 1997; Irons et al 2000; Wiens et al 2004), or 3) exposure to hydrocarbons and, by inference, continuing toxic effects from EVOS, as indicated by elevated cytochrome P4501A [CYP1A] activity (Trust et al 2000; Esler et al 2002; Esler 2008; Esler and Iverson 2010). Based on a weight-of-evidence evaluation from several studies, Wiens et al (2010) concluded no indication of continuing population-level impacts, in terms of either abundance or demographics, on Harlequin Ducks from EVOS.…”
Section: Introductionmentioning
confidence: 99%
“…The pigeon guillemot (Cepphus columba) was the only species which is both common during summer and showing consistent declines in overall abundance compared to pre-spill data. Day et al (1995Day et al ( , 1997 used data from the same surveys and analyzed the abundance of 42 species of marine -oriented birds in relation to an oiling gradient. In order to minimize confounding natural variance 26 habitat features of the bays were included in the analysis as well.…”
Section: Evidence Of Population Impacts After Oil Spillsmentioning
confidence: 99%
“…Using a higher alpha value will increase the power of the test. This was the approach used by Day et al (1995) which used alpha levels up to 0.2 in testing the impact of the Exxon Valdez Oil Spill on marine birds (see chapter 3). Mapstone (1995) suggests a procedure for selecting alpha and beta values where a critical effect size is chosen and given primacy.…”
Section: Science and The Precautionary Principlementioning
confidence: 99%
“…Harlequin Ducks are particularly vulnerable to the direct effects of oil spills because they exhibit high site-fidelity and spend most of their time in intertidal and nearshore waters where they feed on epibenthic invertebrates (King and Sanger 1979; Piatt et al . 1990; Day et al 1995, 1997; Holland-Bartels et al . 1998; Esler et al .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported decreased abundance, linking it to: (1) reduced overwintering survival of females and/or unsuccessful reproduction (Esler et al 2000; Patten et al 2000); (2) degraded habitat quality (Day et al 1995, 1997; Irons et al . 2000; Wiens et al 2004); or (3) exposure to hydrocarbons and, by inference, continuing toxic effects from EVOS, as indicated by elevated cytochrome P4501A [CYP1A] activity (Trust et al 2000; Esler et al 2002; Esler 2008).…”
Section: Introductionmentioning
confidence: 99%